1990
DOI: 10.1021/bi00455a004
|View full text |Cite
|
Sign up to set email alerts
|

Desmethionine alkylamide bombesin analogs: a new class of bombesin receptor antagonists with potent antisecretory activity in pancreatic acini and antimitotic activity in Swiss 3T3 cells

Abstract: Bombesin-related peptides have a large number of physiological functions as well as having an autocrine growth mechanism for the regulation of small cell lung cancer cells. In the present study we have synthesized 21 des-Met amide or alkylamide analogues of bombesin and compared their abilities to function as bombesin receptor antagonists in guinea pig pancreatic acini and Swiss 3T3 cells with those of the previously most potent antagonist described, [Leu13 psi(CH2NH)Leu14]bombesin (analogue I). All des-Met an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 39 publications
4
65
2
1
Order By: Relevance
“…At present, the explanation for the differences from the study on [Ca 2ϩ ] i (4) is unclear. The differences are not due to inactivity of the peptide in our study, because it had a high affinity for the GRP-R, as reported previously (13,29). It remains possible that, in contrast to the GRP-R and NMB-R, there could be large receptor spareness in hBRS-3 receptors such that minimal changes in receptor occupation cause marked changes in [Ca 2ϩ ] i , and therefore the biologic activity dose-response curve for agonist-induced changes in [Ca 2ϩ ] i is far to the left of the receptor occupation curve.…”
Section: Brs-3 Receptor Pharmacologysupporting
confidence: 86%
“…At present, the explanation for the differences from the study on [Ca 2ϩ ] i (4) is unclear. The differences are not due to inactivity of the peptide in our study, because it had a high affinity for the GRP-R, as reported previously (13,29). It remains possible that, in contrast to the GRP-R and NMB-R, there could be large receptor spareness in hBRS-3 receptors such that minimal changes in receptor occupation cause marked changes in [Ca 2ϩ ] i , and therefore the biologic activity dose-response curve for agonist-induced changes in [Ca 2ϩ ] i is far to the left of the receptor occupation curve.…”
Section: Brs-3 Receptor Pharmacologysupporting
confidence: 86%
“…Structure-function studies of all natural occurring bombesin-related peptides for BB 2 and BB 1 receptors suggested that primarily the presence of His for Leu and to a lesser extent the presence of Leu for Phe were the most important differences in GRP from NMB determining high affinity and selectivity for the BB 1 receptor (Lin et al, 1996). Correlating biological activity with binding affinity, especially of antagonists, demonstrated that the presence of a COOH-terminal amino acid in position 14 of bombesin is not essential for high affinity for the BB 2 receptor, but it is essential for biologic activity Wang et al, 1990aWang et al, , 1992.…”
mentioning
confidence: 99%
“…From studies correlating binding results with biological activity, especially for COOH-terminal pseudopeptides, a model was proposed for the biologically active conformation of GRP/Bn at the BB 2 receptor (Coy et al, , 1991bWang et al, 1990a). In a study of the effects on the affinity and potency of bombesin for the BB 2 receptor of substitution of a bond (i.e., CH 2 NH 2 instead of CONH) between each amino acid pair at the COOH terminus, it was found only 13-14 and 9 -10 substitutions resulted in peptides that retained affinity for the BB 2 receptor but did not activate it and thus functioned as antagonists.…”
mentioning
confidence: 99%
See 2 more Smart Citations